2010
DOI: 10.1590/s0104-12902010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Análise do exercício de competências dos não médicos para atenção à maternidade

Abstract: ResumoEstudo descritivo e exploratório realizado com o objetivo de analisar o exercício das competências para atenção à maternidade por profissionais não médicos que atuavam em serviços públicos de saúde de uma região da cidade de São Paulo. Para isso, foi realizada caracterização dos serviços e dos profissionais, identificação das atividades que desempenhavam e sua frequência, e possíveis obstáculos ou dificuldades. O campo de pesquisa foi composto de 59 unidades básicas de saúde e seis hospitais com leitos o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 6 publications
0
9
0
13
Order By: Relevance
“…The author assigned the deficient care provided to the fact that many had failed to keep up with advances and changes in labor care instituted by the Ministry of Health (MOH) for humanized and evidence-based care (17) . Similar results were found with the sample of this research, in which maternity professionals had FHS and maternity unit, and integrated monitoring of pregnant women.…”
Section: Methodsmentioning
confidence: 99%
“…The author assigned the deficient care provided to the fact that many had failed to keep up with advances and changes in labor care instituted by the Ministry of Health (MOH) for humanized and evidence-based care (17) . Similar results were found with the sample of this research, in which maternity professionals had FHS and maternity unit, and integrated monitoring of pregnant women.…”
Section: Methodsmentioning
confidence: 99%
“…The guarantee of a quality prenatal presents proven impact on maternal and perinatal morbidity and mortality 19 . In this regard, it was found that remained practically unchanged the percentage of women who began prenatal care and had at least six visits at birth, in the present study (referring only to 2011), the period evaluated 2004-2008) 13 .…”
Section: -17mentioning
confidence: 99%
“…Desde o final dos anos 80, os enfermeiros vêm conquistando seu espaço na assistência ao parto, resultado disso, foi à inserção na graduação de enfermagem, no Brasil, em 1922, como componente curricular e em 94, como pós--graduação. (1,10,11,12,13,14) Atualmente a especialização em obstetrícia só é permitida para médicos e enfermeiros. (15) Ainda são poucos os enfermeiros obstétricos que atuam realizando parto.…”
Section: Categoria 1: Evolução Da Enfermagem Obstétrica E Da Humanizaunclassified